ECOLODGE SEBAGAI SARANA AKOMODASI PARIWISATA BERKELANJUTAN - Aprilia Kumaji, Rahma; Hakim, Luchman; Pangestuti, Edriana (FIA UB, 2021)
Ecotourism needs accommodation that simple, comfortable, provides unique nature experience, and of course ecologically acceptable. Ecolodges is one of the options for tourist who wants their accomodation to be environmentally friendly. That is why, ecolodge needs to be managed with sustainability principles. This literature review uses a systematic literature review approach. Empirical articles on the topic of ecolodge published between 2009 and 2019 were obtained from three reputable journal portals, totaling 56 articles. The articles are reduced to nine articles which are empirical articles, in English, and having ecolodge as the object of their research. The purpose of this literature review is to see the results of Ecolodge related research that has been conducted. This paper finds that several studies highlight the importance of standardization, solid governance, and partnership for ecolodge development. Other researches addresses the importance of local communities' perception and their capacity building development. Some studies also specifically address ecolodge as a form of indigenous tourism. Findings from several studies also indicate the importance of consumer satisfaction for effectiveness and efficiency in ecolodge management. This paper suggests that in future research directions should be conducted with more involvement from other stakeholders to evaluate ecolodge performance in various aspects.